EVALUATION OF RECLAIMED SURFACE MINES AS WILD TURKEY BROOD RANGE - Roger J. Anderson; David E. Samuel (Wildlife Society Bulletin)
Abstract A surface mine classification system was developed based on subjective evaluation of vegetation types. Five vegetation classifications and a control site (unmined) were tested with two broods (one early and one later) of imprinted wild turkey poults (Meleagris gallopavo silvestris). Feeding behavior and distress reaction observations indicated classes 2 (sapling with grass legume understory) and 5 (primarily volunteer under and overstory) provided the best combination of invertebrate availability and cover density for wild turkey broods when compared to unmined control sites. Classes 1 (grassland), 3 (grassland with pole stage overstory) and 4 (plantation) appeared to be marginal habitat. There was, however, increased feeding observed on class 1 mines during the late brood period. Numbers of invertebrates consumed were directly related to availability. Invertebrate availability was highest on class 2 (P <.05), sites. Class 5 ranked second, but showed no significant difference in invertebrate productivity (P <.05) when compared to unmined control sites. The remaining classes 1, 3 and 4 showed significantly less invertebrate productivity (P >.05) than classes 2, 5 and the unmined control site. Classes 2, 5 and the control provided a denser vegetation mat, hence, better escape cover than classes 1, 3 and 4. Management recommendations are presented.